Implementation and Operational Research: Affordable Care Act Implementation in a California Health Care System Leads to Growth in HIV-Positive Patient Enrollment and Changes in Patient Characteristics. (15th December 2016) - Satre, Derek D.; Altschuler, Andrea; Parthasarathy, Sujaya; Silverberg, Michael J.; Volberding, Paul; Campbell, Cynthia I.
Abstract : Objectives: This study examined implementation of the Affordable Care Act (ACA) in relation to HIV-positive patient enrollment in an integrated health care system; as well as changes in new enrollee characteristics, benefit structure, and health care utilization after key ACA provisions went into effect in 2014. Methods: This mixed-methods study was set in Kaiser Permanente Northern California (KPNC). Qualitative interviews with 29 KPNC leaders explored planning for ACA implementation. Quantitative analyses compared newly enrolled HIV-positive patients in KPNC between January and December 2012 ("pre-ACA, " N = 661) with newly enrolled HIV-positive patients between January and December 2014 ("post-ACA, " N = 880) on demographics; medical, psychiatric, and substance use disorder diagnoses; HIV clinical indicators; and type of health care utilization. Results: Interviews found that ACA preparation focused on enrollment growth, staffing, competition among health plans, concern about cost sharing, and HIV pre-exposure prophylaxis (PrEP) services. Quantitative analyses found that post-ACA HIV-positive patient enrollment grew. New enrollees in 2014 were more likely than 2012 enrollees to be enrolled in high-deductible plans ( P < 0.01) or through Medicaid ( P < 0.01), and marginally more likely to have better HIV viral control ( P < 0.10). They also were more likely to be diagnosed with asthma ( P < 0.01) or substance use disorders ( P < 0.05) and to have used primary care health services in the 6 months postenrollment ( P < 0.05) than the pre-ACA cohort. Conclusions: As anticipated by KPNC interviewees, ACA implementation was followed by HIV-positive patient enrollment growth and changing benefit structures and patient characteristics. Although HIV viral control improved, comorbid diagnosis findings reinforced the importance of coordinated health care. Abstract : Supplemental Digital Content is Available in the Text.